Penurunan Konsentrasi Besi dan Mangan Terlarut pada Air Tanah Muara Lawa Menggunakan Serbuk Kiambang (Salvinia molesta) - Widodo, Nanang Tri; Sari, Ika Yekti Liana; Pratiwi, Djihan Ryn (Journal of Science and Technology: Alpha, 2025)
One of the primary sources of water for human needs is groundwater. Groundwater serves various household purposes, such as bathing, cooking, drinking, and washing. The presence of iron and manganese in groundwater has long been a serious concern, as these elements can impart an unpleasant taste and odor to the water. This study aims to determine the reduction levels of dissolved iron and manganese concentrations in groundwater using powdered water fern (Salvinia molesta) as an adsorbent. The reduction of iron and manganese concentrations was carried out by adsorbing these elements from groundwater using activated powdered water fern. The results showed that the concentrations of iron and manganese in the groundwater were reduced by 64.77% and 77.67%, respectively.